Fructose‐1,6‐bisphosphatase aggravates oxidative stress‐induced apoptosis in asthma by suppressing the Nrf2 pathway - Hu, Jiapeng (J Cell Mol Med, 2021)
Asthma is a chronic airway disease that causes excessive inflammation, oxidative stress, mucus production and bronchial epithelial cell apoptosis. Fructose‐1,6‐bisphosphatase (Fbp1) is one of the rate‐limiting enzymes in gluconeogenesis and plays a critical role in several cancers. However, its role in inflammatory diseases, such as asthma, is unclear. Here, we examined the expression, function and mechanism of action of Fbp1 in asthma. Gene Expression Omnibus (GEO) data sets revealed that Fbp1 was overexpressed in a murine model of asthma and in interleukin (IL)‐4‐ or IL‐13‐stimulated bronchial epithelial cells. We confirmed the findings in an animal model as well as Beas‐2B and 16HBE cells. In vitro investigations revealed that silencing of Fbp1 reduced apoptosis and the proportion of cells in the G2/M phase, whereas overexpression led to increases. Fbp1 knock‐down inhibited oxidative stress by activating the nuclear factor erythroid 2‐related factor 2 (Nrf2) pathway, whereas Fbp1 overexpression aggravated oxidative stress by suppressingthe Nrf2 pathway. Moreover, the Nrf2 pathway inhibitor ML385 reversed the changes caused by Fbp1 inhibition in Beas‐2B and 16HBE cells. Collectively, our data indicate that Fbp1 aggravates oxidative stress‐induced apoptosis by suppressing Nrf2 signalling, substantiating its potential as a novel therapeutic target in asthma.